The limited role of elective neck dissection in patients with cN0 salivary gland carcinoma. Issue 1 (January 2019) - Qian, Kai; Guo, Kai; Zheng, Xiaoke; Sun, Wenyu; Sun, Tuanqi; Chen, Lili; Ma, Ding; Wu, Yi; Ji, Qinghai; Wang, Zhuoying
Abstract: Purpose: To evaluate whether elective neck dissection (END) was beneficial for cN0 patients with salivary gland carcinoma. Materials and methods: The rates of regional failure-free survival and disease-free survival were calculated using Kaplan–Meier methods and Cox models. The risk factors for occult lymph node metastasis (OLNM) in cN0 patients undergoing END was analyzed using logistic regression. A nomogram was formulated to calculate the estimated probability of OLNM. Results: Neck dissection was performed in 84 patients (43.3%). OLNM was detected in eight of the patients who underwent END. During the follow-up period, regional recurrences involving cervical lymph nodes were found in 10 patients. Cox model analysis revealed that neck dissection was not related to regional failure-free survival and disease-free survival. Logistic regression analysis revealed that older age, neural symptoms, and positive adjacent lymph nodes were associated with OLNM. A nomogram comprising age, neural symptoms, and adjacent lymph nodes was developed to predict the risk of OLNM. Conclusion: The incidence of OLNM was low in cN0 patients after detailed preoperative evaluations. There was no strong evidence supporting END as a conventional therapy in cN0 patients with salivary cancers. Our nomogram is a simple and practical instrument for strengthening the prediction of OLNM.